CRITICAL READING SKILLS, ACADEMIC VOCABULARY MASTERY, AND ARGUMENTATION WRITING SKILLS - Kokom Nurjanah; Santi Setiyaningsih (UNIVERSITAS PAKUAN, 2022)
The purpose of this study was to investigate argumentation writing skills in terms of critical reading and student academic vocabulary mastery. This research was conducted at the Department of English Education, Semester VII, STKIP Kusuma Negara Cijantung. The research method used is a correlation survey with technical regression analysis. Collecting data from research variables using test instruments. The results of this study reveal that: (1) critical reading has a positive effect on students' argumentation writing skills; (2) academic vocabulary mastery has a positive influence on students' argumentative writing skills; and (3) critical reading and mastery of academic vocabulary have a positive influence on students' argumentative writing skills. Therefore, it can be concluded that the improvement of critical reading skills, mastery of academic vocabulary supports the improvement of students' argumentation writing